Effect of coupling reactions on the mechanical and biological properties of tropical wood polymer composites (WPC) - Islam, M.S.; Hamdan, S.; Hasan, M.; Saleh, A.A.; Rahman, M.R. (Elsevier Ltd, 2012)
Wood polymer composites (WPCs) based on five types of selected Malaysian tropical light hardwood species were prepared using a methyl methacrylate (MMA) and hexamethylene diisocynate (HMDIC) monomer mixture at a 1:1 ratio. Before being impregnated with MMA/HMDIC, the wood species were chemically pretreated with benzene diazonium salt for the coupling reaction with wood and to increase adhesion and compatibility of the wood fiber to the polymer matrix. The monomer mixture (MMA/HMDIC) was impregnated into both the raw wood and diazonium salt pretreated wood specimens to manufacture wood polymer composites (WPC) and pretreated wood polymer composites (PWPC), respectively. Microstructural analysis (scanning electron microscopy and Fourier transform infrared spectroscopy) and mechanical (three-point bending and compression) and biological (fungal decay resistance) tests were conducted. Comparisons were made among the properties of raw wood, WPC, and PWPC. The results reveal that PWPC yielded better mechanical and biological properties compared to untreated WPC and raw wood.